Socio-Economic Impact Assessment of Dam Break: A Case Study of Hulu Perak Dams in Malaysia - Salleh R.; Mohd Sidek L.; Abdul Rashid R.; Basri H.; Kumar V.; Abd Razak S.N.; Khalid Ali K.; Singh P. (Springer Science and Business Media Deutschland GmbH, 2025)
In Malaysia, embankment dams are frequently constructed because they benefit the local population, particularly in agricultural activities and flood control. However, flood disasters caused by dam breaks have catastrophic consequences on human lives and immensely damage the environment, infrastructure, and socio-economic stability, especially in downstream areas. Despite the rapid advancement of risk analysis in dam engineering, there is limited research on the socio-economic impact of dam failure. This paper is deemed to provide a critical review of the socio-economic risks affected by dam breaks in Hulu Perak district, Malaysia. The findings have highlighted the communities, key facilities, and heritage sites are at high risk if there are dam breaks in the Hulu Perak district. ?t is recommended that appropriate risk management measures be undertaken to reduce human catastrophy and negative socio-economic impacts. Hence, there is a need to conduct an empirical study to assess dam break threats to humans and the socio-economy and formulate a framework to mitigate the risks of flood disasters due to dam failures. ? 2024, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.